The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s12192-020-01134-9
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of HSPA5 (Grp78, BIP) with negatively charged phospholipid membranes via oligomerization involving the N-terminal end domain

Abstract: Heat shock proteins (HSPs) are ubiquitous polypeptides expressed in all living organisms that participate in several basic cellular processes, including protein folding, from which their denomination as molecular chaperones originated. There are several HSPs, including HSPA5, also known as 78-kDa glucose-regulated protein (GRP78) or binding immunoglobulin protein (BIP) that is an ER resident involved in the folding of polypeptides during their translocation into this compartment prior to the transition to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 66 publications
(101 reference statements)
0
13
0
Order By: Relevance
“…The interaction of HSPA5 with artificial lipid bilayers (liposomes) has confirmed membrane insertion, displaying a high affinity for negatively charged phospholipids (Dores-Silva et al 2020b). Both HSPA5 N-terminal and C-terminal domains could independently interact with phospholipid membranes, but not at the same levels as the full-length protein, suggesting that the two regions may be involved in membrane insertion (Dores-Silva et al 2020b).…”
Section: The Interaction Of Hsp70s With Lipids and Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of HSPA5 with artificial lipid bilayers (liposomes) has confirmed membrane insertion, displaying a high affinity for negatively charged phospholipids (Dores-Silva et al 2020b). Both HSPA5 N-terminal and C-terminal domains could independently interact with phospholipid membranes, but not at the same levels as the full-length protein, suggesting that the two regions may be involved in membrane insertion (Dores-Silva et al 2020b).…”
Section: The Interaction Of Hsp70s With Lipids and Membranesmentioning
confidence: 99%
“…However, HSPA5 needs to overcome the ER retention signal (KDEL) to reach the cell surface/extracellular environment, which could be a consequence of ER stress (Zhang et al 2013) or any additional factors. HSPA5 is unlikely to interact with the internal ER membrane because the phospholipid composition of this region does not support membrane insertion (Dores-Silva et al, 2020b). Several domains of HSPA5 have been proposed to be inserted into the plasma membrane, particularly the C-terminus end (Tsai et al 2015;Tseng et al 2019).…”
Section: The Interaction Of Hsp70s With Lipids and Membranesmentioning
confidence: 99%
“…Interestingly, Nakatsuka et al showed that vaspin binds GRP78 via the helical domains in the N-terminus and not by the RCL region [ 38 ]; the binding site in GRP78 remains unknown. Nevertheless, the mechanism of signal transduction into the cell is also unknown and probably depends on high GRP78 affinity for negatively charged cell membrane phospholipids [ 53 ]. Vaspin also binds to phospholipids, which play a major role in membrane trafficking [ 54 ].…”
Section: Vaspin Receptor Grp78 and The Mechanism Of Vaspin Actionmentioning
confidence: 99%
“…In addition to its strong antiapoptotic properties, GRP78 is also closely related to tumor proliferation and survival. Studies have shown that GRP78 is one of the key regulators of tumor resistance and is closely related to tumor recurrence and metastasis [ 13 , 14 ]. The Wnt signaling pathway is a group of signal transduction pathways that includes multiple downstream channels that are stimulated by the binding of ligand proteins to membrane protein receptors.…”
Section: Introductionmentioning
confidence: 99%